Endogenous monopsony and the perverse effect of the minimum wage in small firms - Leif Danziger (Institute for the Study of Labor (IZA), 2009)
The minimum wage rate has been introduced in many countries as a means of alleviating the poverty of the working poor. This paper shows, however, that an imperfectly enforced minimum wage rate causes small firms to face an upward-sloping labor supply schedule. Since this turns these firms into endogenous monopsonists, the minimum wage rate has the perverse effect of reducing employment in small firms as well as what these firms offer their workers. Thus, if there are only small firms, the minimum wage rate makes all workers that would be employed in the absence of a minimum wage rate worse off.
urn:nbn:de:101:1-20090825591
Keywords: J38; 330; Endogenous monopsony; minimum wage; noncompliance; small firms; Mindestlohn; Klein- und Mittelunternehmen; Arbeitsnachfrage; Monopson; Beschäftigungseffekt; Normbefolgung; Theorie